Study Literature Hasil Belajar Sosiologi dengan Model Pembelajaran Talking Stick - Yosefina Inya Kodi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2023)
The study aims to review several articles from Google Scholar about the implementation of the learning stick method in sociology. The article criteria were published in 2015-2020. The study showed that the Talking Stick model does not only improve the students` stick outcomes, but it can also produce the students` abilities in critical thinking, communication skills, cooperative abilities, and problem-solving abilities. The students can exchange their ideas with friends, which makes the students more active in stick because they are in stick to provide information about the material being studied.